Comparative study of I-V methods to extract Au/FePc/p-Si Schottky barrier diode parameters - Oruc, Cigdem; Altindal, Ahmet (SPRINGER HEIDELBERG, 2018)
So far, various methods have been proposed to extract the Schottky diode parameters from measured current-voltage characteristics. In this work, Schottky barrier diode with structure of Au/2(3),9(10),16(17),23(24)-tetra(4-(4-methoxyphenyl)-8-methylcoumarin-7 oxy) phthalocyaninatoiron(II) (FePc)/p-Si was fabricated and current-voltage measurements were carried out on it. In addition, current-voltage measurements were also performed on Au/p-Si structure, without FePc, to clarify the influence of the presence of an interface layer on the device performance. The measured current-voltage characteristics indicate that the interface properties of a Schottky barrier diode can be controlled by the presence of an organic interface layer. It is found that the room temperature barrier height of Au/FePc/p-Si structure is larger than that of the Au/p-Si structure. The obtained forward bias current-voltage characteristics of the Au/FePc/p-Si device was analysed by five different analytical methods. It is found that the extracted values of SBD parameters strongly depends on the method used.
Keywords: CURRENT-VOLTAGE CHARACTERISTICS; SERIES RESISTANCE; TEMPERATURE-DEPENDENCE; IDEALITY FACTOR; HEIGHT; PLOT; PHTHALOCYANINES; CELLS; Materials Science; Physics